2020
DOI: 10.1016/j.jhin.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Wearing of face masks by healthcare workers during COVID-19 lockdown: what did the public observe through the French media?

Abstract: Wearing a face mask is a major issue in the fight against the spread of the COVID-19 pandemic. The French general population widely started to wear this personal protective equipment usually dedicated to healthcare workers, without being educated to its correct use. People base their behaviour on what they see in the media. However, we observed that mask wearing of healthcare workers published in the media during the pandemic only conformed to good practice guidelines in 70.8% of the photographs collected on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…In the first weeks of March, adapted organisation and personal protective equipment were available in the COVID-19 sector of the hospital only. 26 This is now known to have been a preventive factor for mental health burden during the crisis, as were collective support and a sense of work, already described by psychologists and in the literature. Together, these factors could explain the absence of higher impact on front-line workers.…”
Section: Discussionmentioning
confidence: 92%
“…In the first weeks of March, adapted organisation and personal protective equipment were available in the COVID-19 sector of the hospital only. 26 This is now known to have been a preventive factor for mental health burden during the crisis, as were collective support and a sense of work, already described by psychologists and in the literature. Together, these factors could explain the absence of higher impact on front-line workers.…”
Section: Discussionmentioning
confidence: 92%
“…The authors concluded that HCWs reported more anxiety, depression, and sleep problems than the general population, a finding echoed by other reviews in this field [3,4]. Female gender, direct contact with COVID-19 patients and the lack of personal protective equipment (PPE) were significant risk factors for higher prevalence of mental health problems in HCWs [1][2][3][4][5][6]. In a report of a Spanish association published in May 2020, 86.8% of physicians considered that they could have been a vector of the disease because they lacked adequate protective material [7].…”
Section: Introductionmentioning
confidence: 86%
“…Health officials have recommended that medical-grade face masks, such as respirators, be prioritized for use by medical personnel to prevent the shortage of supply for this product. Meanwhile, cotton masks are recommended for the public [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the early stages of the pandemic, public health messages about wearing masks were inconsistent, conflicting, and tinged with contemptuous comments, which caused public discontent and even confusion. Eventually, the recommendations have evolved in lockstep with scientific understanding [ 8 ].…”
Section: Introductionmentioning
confidence: 99%